Evaluating the impact of small-scale mining on the achievement of the sustainable development goals in Guyana. Issue 116 (February 2021) - Laing, Timothy; Moonsammy, Stephan
Highlights: Artisanal and small-scale mining has both positive benefits and negative costs. Mapping impacts of ASM on to the SDGs shows the positive and negative contributions it can have to achieving these goals. Valuing ecological, economic and social impacts of ASM in Guyana shows the value the industry can have to the country. Abstract: The artisanal and small-scale mining (ASM) sector in Guyana has, over the last decade, become the main engine for economic growth, the key source of foreign exchange and a vital source of employment across the country. It has therefore served as a vital driver in alleviating poverty and helping the country to make progress on the Sustainable Development Goals (SDGs) relating to poverty and economic growth. At the same time, however, the sector has contributed to significant levels of deforestation and water pollution, threatening progress on other SDGs. In this paper we develop a framework that allows an evaluation of the impact of the sector upon progress towards a variety of the relevant SDGS and their accompanying targets and indicators. We extend this framework by presenting valuations of the environmental and social impacts from the ASM sector and compare this to the economic benefit from the sector in terms of contribution to GDP, foreign exchange, taxation and indirect employment benefits, allowing us to understand the trade-offs involved in the use of the ASM sector as a tool for achieving the SDGs. Our assessment shows prominent economic benefits crucial for the country to achieve the economic related SDG targets but at a significant social and environmental cost that will hinder the country achieving the social and ecological SDG targets. The framework presented in this paper can thus be used to identify policy areas that need prioritizing in order to address the social and ecological costs associated with ASM whilst maintaining and possibly improving the economic prosperity it provides.